HUBUNGAN DUKUNGAN KELUARGA DENGAN TAHAP HIPERTENSI - Wandira, Marya Nasti; Nurchayati, Sofiana; Safri, Safri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Hypertension is an increased blood pressure above normal seen from systolic or diastolic rates based on blood pressure measurement results. Hypertensive patients need family support, this is closely related to the implementation of patient hypertension management that will affect the patients blood pressure. The purpose of study was to identify the correlation between family support and hypertension stage. The design was descriptive correlational with cross sectional approach. The number of samples of this study are 73 people were selected using purposive sampling with inclusion criteria. This research used questionnaire that has been tested in validity and reliability, and this research used sphygmomanometer to determine the hypertension stage. The analysis used was univariate analysis distribution frequency and bivariate with Chi-square test. The results showed that there was a significant relationship between family support and hypertension stage with p-value=0.014 < Î± (0.05). Based on the results of this study, it is expected that the family can help patients in the management of hypertension to help reduce the patients blood pressure. Â Â Keywords :Family Support, Hypertension, Hypertension Stage